Core–Shell Nitrogen‐Doped Carbon Hollow Spheres/Co3O4 Nanosheets as Advanced Electrode for High‐Performance Supercapacitor. Issue 12 (31st January 2018) - Liu, Tao; Zhang, Liuyang; You, Wei; Yu, Jiaguo
Abstract: Co3 O4 /nitrogen‐doped carbon hollow spheres (Co3 O4 /NHCSs) with hierarchical structures are synthesized by virtue of a hydrothermal method and subsequent calcination treatment. NHCSs, as a hard template, can aid the generation of Co3 O4 nanosheets on its surface; while SiO2 spheres, as a sacrificed‐template, can be dissolved in the process. The prepared Co3 O4 /NHCS composites are investigated as the electrode active material. This composite exhibits an enhanced performance than Co3 O4 itself. A higher specific capacitance of 581 F g −1 at 1 A g −1 and a higher rate performance of 91.6% retention at 20 A g −1 are achieved, better than Co3 O4 nanorods (318 F g −1 at 1 A g −1 and 67.1% retention at 20 A g −1 ). In addition, the composite is employed as a positive electrode to fabricate an asymmetric supercapacitor. The device can deliver a high energy density of 34.5 Wh kg −1 at the power density of 753 W kg −1 and display a desirable cycling stability. All of these attractive results make the unique hierarchical Co3 O4 /NHCS core–shell structure a promising electrode material for high‐performance supercapacitors. Abstract : The Co3 O4 /N‐doped carbon hollow sphere (Co3 O4 /NHCS) with a core–shell structure, where Co3 O4 nanosheets serve as the shell and NHCS as the core, has large surface area and hierarchical porous structure. The asymmetric supercapacitor assembled with Co3 O4 /NHCS as a positive electrode and activated carbon as a negative electrode exhibits an excellent electrochemical performance.